Testing and training specific motor abilities in elite junior soccer players - Müller, E. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Several recently published studies show that physical demands in elite soccer have increased significantly. The challenge in talent promotion of young soccer players lies in the necessity to create long term strategies in developing soccer specific motor abilities. Therefore attending this process with scientifically based diagnostic systems as well as documentation and guidance in designing the training-regime becomes an essential need. The Austrian Soccer Association initiated an eight years prospective study testing soccer specific abilities twice a year of all elite junior soccer players at the age of 13 - 20. This test battery (14 tests) mainly includes tests for sprinting, coordination, jumping and endurance abilities. In the meantime data of more than 3500 subjects have been analyzed. Factor analyses show a five fold dimension of motor skills for the players aged 13 - 17. The factors grouped in: speed/strength, coordination, power and specific endurance. For the 18 - 20 years old players the dimensions are reduced to speed/coordination, strength/power and endurance. Age dependent differences in the various abilities were analyzed, too. Most of the soccer specific abilities show a continuous development until the age of 17. But between 17 and 20 years elite soccer players on average show no significant increase in the test items speed, coordination and power. The next step of this project was to develop specific training methods and exercises to improve soccer specific speed, coordination and power abilities and to evaluate these methods in a three months training intervention study with 19 years old elite soccer players.